GENERASI Y DAN ADOPSI TERHADAP INTERNET BANKING PADA NASABAH DI INDONESIA MENGGUNAKAN KERANGKA TECHNOLOGY ACCEPTANCE MODEL (TAM) - Yuliyani; Arief Budiman; Maya Sari Dewi (JWM (JURNAL WAWASAN MANAJEMEN), 2016)
The purposes of this study were to describe and to analyze the Y Generation and Adoption of Internet Banking on bank customers in Indonesia using TAM model. The results of this study showed that the variables of perceived usefulness and perceived ease of use had a positive and significant correlation directly towards the attitude in using perceived usefulness, and also had a positive influence and directly towards the actual usage while perceived ease of use does not affect actual usage. Attitude towards using has a positive and significant correlation directly towards the actual usage